Tools to reduce inappropriate drug use in geriatric patients: PRISCUS 2.0 list updates - Şeyma Handan Akyön; Kamile Sılay; Petra A. Thürmann (Archives of Gerontology and Geriatrics Plus)
Introduction: Polypharmacy, the concurrent use of multiple medications, poses significant risks to geriatric patients due to increased susceptibility to side effects and interactions. This narrative review addresses the challenges posed by polypharmacy in older adults, emphasizing the importance of reducing adverse effects. The article examines explicit, implicit, and mixed assessment tools used to identify potentially inappropriate medications (PIMs) and minimize adverse effects in geriatric populations. Conclusion: The article underscores the critical need for accurate assessment and intervention to mitigate the negative consequences of polypharmacy in geriatric patients. The PRISCUS 2.0 List, an extensively updated version of the original PRISCUS list, emerges as a comprehensive tool to aid healthcare professionals in identifying PIMs. Its expanded medication list, incorporation of new evaluation criteria, disease-specific considerations, and enhanced classification system contribute to better identification of inappropriate medications. When we compared with other PIM criteria in previous studies, the EU(7)-PIM list was one of the most comprehensive, and with the PRISCUS 2.0 list update, it was determined that it contains partially more drugs that are inappropriate for the elderly in the Turkish pharmaceutical market. Comparisons between various criteria reveal their varying detection rates and strengths, highlighting the significance of using multiple criteria for a more holistic assessment. Additionally, the advent of online applications offers accessible solutions by consolidating multiple explicit criteria into a single platform, aiding practitioners in making well-informed decisions. The study emphasizes the need for ongoing updates, validation, and suitability assessments for these tools in diverse healthcare settings to ensure their effectiveness.